Republic of Congo Economic Update, September 2014 : The Road to Economic Development - World Bank (World Bank, Washington, DC, 2014)
Congo's current growth trend is lower than the projected rate of growth in the 2012-2016 National Development Plan (NDP). Congo should continue investing intensively but more efficiently in infrastructure, an urgent need. Ample evidence shows that investment efficiency in infrastructure is critical for economic development. Given the importance of this issue for the future growth trajectory of the country, the second part of the update focuses on efficient investment in infrastructure. By focusing on improving government efficiency, the Republic of Congo would be well positioned to achieve sustained and diversified growth, rather than continuing on the current path that is largely driven by higher levels of public investment. The Congolese government can achieve better public investment outcomes by implementing sound public financial management policies in these areas. These include better preparation and planning of investment projects, introduction of systems-based commitment of reform in the procurement and disbursement system to speed up the processes and make them more transparent.